Hubungan Manajemen Karir dan Komitmen Organisasi (Lembaga Pengembangan Kinerja Dosen, 2021)
Career is one form of organizational appreciation to workers. This needs to be observed carefully so that it can be a motivating factor for workers. In addition, organizational commitment is a form of employee loyalty to the organization. Both contribute to the empowerment of people in the organization. This research was conducted to prove whether there is a relationship between career management and organizational commitment so that the type of research conducted is correlational research. A total of 98 employees working in PT ABC will be selected to be set as the sample. The sample is determined by the census technique. The researcher uses primary data obtained from the results of questionnaires that have been answered by employees. This study resulted in the finding that there is indeed a relationship between career management variables and organizational commitment.